El Clima Organizacional de la Empresa Lavanser S.A.S., Desde la Perspectiva del Personal Operativo - Benavides Sotomonte, Sandra Leonor (Universidad Antonio Nariño, 2024)
This research describes the characteristics of the company's organizational climate. Lavanser S.A.S. A quantitative-descriptive methodology was used with a design transversal through the application of the RE04 Operational Work-Personal Climate Survey GH provided by the same company and adapted by the author of this research to a sample of 120 people from operational personnel. According to the results obtained, the Categories that gave a high unfavorable percentage were: Training and Work Environment. HE It also concludes that there are difficulties in communication between colleagues.